Examining The Shift in The Procedural Law of The Administrative Court: Discourse on Changes in Society and The Judiciary - M. Ikbar Andi Endang; Moh. Fadli; Istislam; Dewi Cahyandari (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Shifting the procedural law of the Administrative Court is a necessity. This happened as an effort to respond to the absence of arrangements for resolving administrative disputes and government administration regulated in sectoral laws. The Supreme Court through Perma responded to the void in legislations regarding the procedures or procedures for this matter. To analyze the context, this study uses a legal approach, a historical approach, and a conceptual approach. Based on the analysis, it can be seen that there is a shift in the conservative setting from the procedural law of the Administrative Court towards a procedural law system with a progressive setting nuance. This can be seen with changes in procedures, both in terms of reducing the levels of examination, reducing the process of proceedings, and determining the grace period for the event process. With this progressive system, the renewal of the case administration system and the electronic trial go hand in hand. Interpreting the dynamics between law and the judiciary with changes in society, the momentum for changes in the procedural law of the Administrative Court with social changes in society accommodates legal certainty and the principles of a simple and fast trial. Consequently, the shift in the character of the Administrative Court requires proper legislation in a law that regulates the procedural law of the Administrative Court